HUMAN RIGHTS IN A FAMILY SETTING JODI PICOULT’S MY SISTER’S KEEPER - Wuisan, Cindy; Lolowang, Imelda S.; Andries, Fivy A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research aims to explain the human rights contained in My Sister’s Keeper and the sociological factors of cultural, economic, and educational relations. The problem studied is how human rights in the family environment are reflected in the novel My Sister’s Keeper, which is then analyzed using a qualitative descriptive method with a sociological approach. The results of the analysis obtained show that the whole highlights the struggles faced by the Fitzgerald family resulting in neglect of the needs of others. This neglect of the needs of others is the critical point of tension and conflict in family dynamics throughout the story, as well as the strong dedication of each family member in carrying out their respective roles as outlined in the Murdock framework. The central theme of this paper revolves around the strong dedication of each family member to their respective roles and explores their characters and relationships within the context of this framework.